Haematopoietic stem cell transplantation for poor-prognosis systemic sclerosis. (6th May 2015) - van Laar, Jacob M.; Naraghi, Kamran; Tyndall, Alan
Abstract: Haematopoietic stem cell transplantation (HSCT) following intensive immune suppression has been used in >2000 patients with severe autoimmune diseases for 18 years, including 300 with SSc. The concept is to profoundly reduce the bulk of auto-aggressive immune competent cells and then rescue the patient's ablated haematopoiesis via an autologous HSCT. An early analysis of uncontrolled phase I/II data suggested that approximately one-third of these achieved a substantial improvement, with a relapse rate of 25% and a treatment-related mortality ranging from 6% to 23% across different studies. These early results led to three prospective randomized controlled trials, two of which are completed, confirming that HSCT shows clear advantages over conventional immunosuppression, but with significant toxicity. In some patients, sustained complete normalization of skin changes, reversal of positive autoantibody status and withdrawal of immunosuppressive medication were observed. These results attest to the profound effects of HSCT.